Redução de arrasto induzida por polímeros em escoamento turbulento de águas de mananciais - Lima, Diogo de Azevedo (2018)
It is known that in the non-particulate water the hydraulic drag can be reduced drastically, adding some parts per million (ppm) of certain high molecular weight polymeric additives. This phenomenon known as drag reduction, reported for the first time by Toms (1948), has attracted both the academic interests and the industrial interests, due to the importance and applicability in the transport of liquids in pipes. However, the hydraulic transport of solids in tubes is presented as possible industrial use of the drag reduction effect. In this way, this research is interested in investigating the behavior of the drag reducing polymers in the flow of water with different concentrations of particulates, through a sequence of tests conducted on an experimental bench composed of asystem of pipes in series. In this work, water obtained directly from springs and laden with sediments with three different concentrations of solids will be used. In experiments, using polyethylene oxide (PEO), xanthan gum (XG) and okra powder (composed of natural fibers and polymers of okra) at concentrations of 50 ppm, 100 ppm and 200 ppm it is possible to assess which polymers are most efficient in each condition along the experiment time and the influence of suspended solids on polymer-induced drag reduction. The results show that, for the concentrations of solids used in the research, there is no significant change in the behavior of PEO and XG, showing that they can be diluted in these solvents without significant loss of the efficiency of the drag reducer. However, for okra powder, for certain concentrations of the polymer and solids in the solvent, variations in the efficiency of the drag reducer agent occur when compared to the non-particulate solution